Interaction of physostigmine with three injectable anaesthetics in a young chick model - H. M. S. Garmavy; F. K. Mohammad (Bulgarian Journal of Veterinary Medicine)
Propofol, thiopental and ketamine are injectable general anaesthetics with different mechanisms of action. Reports vary with respect to the antagonistic action of physostigmine against these anaesthe¬tics. The purpose of the present study was to examine the possible interaction of physostigmine with the anaesthetic action of the three anaesthetics in a model of young chicks (7–14 days old). Chicks (8/group) were anaesthetised with propofol at 10 mg/kg, intraperitoneally (i.p.), thiopental at 20 mg/kg, i.p. and ketamine at 10 mg/kg, intramuscularly (i.m.). The anaesthetised chicks were subjected to treatment challenges with physostigmine (0.25 mg/kg, i.p.) or neostigmine (0.125 mg/kg, i.p.), 5 minutes before the anaesthetic injection or after the induction of anaesthesia. When physostigmine was injected before anaesthesia, it prevented propofol but not thiopental or ketamine anaesthesia. Physostigmine given after the anaesthesia reduced the sleep time of propofol, but not those of thio-pental or ketamine in chicks. Neostigmine treatments did not significantly affect the anaesthesia in-duced by the three anaesthetics in chicks. The median effective doses (ED50) of the anaesthetics in chicks were determined by the up-and-down method with or without concomitant physostigmine (0.25 mg/kg, i.p.) after the loss of the righting reflex. The ED50 values of propofol, thiopental and ketamine in chicks were 7.712 mg/kg, i.p., 14.744 mg/kg, i.p. and 10.168 mg/kg, i.m., respectively. Physostigmine differentially increased the ED50 of propofol by 137%, and did not affect those of the thiopental and ketamine. Plasma cholinesterase activity was significantly reduced in the propofol and thiopental anaesthetic groups of chicks, whereas that of the ketamine group was not affected. In conclusion, the results suggest that physostigmine, being a cholinergic stimulant, could specifically antagonise propofol anaesthesia in the young chick model, with clinical trial awaiting further studies.